Effect of surface treatments on microstructure and stress corrosion cracking behavior of 308L weld metal in a primary pressurized water reactor environment. (15th April 2020) - Dong, Lijin; Zhang, Xiaolong; Han, Yaolei; Peng, Qunjia; Deng, Ping; Wang, Shuliang
Highlights: Milling, mechanically grinding and electropolishing promote SCC of 308L weld metal. Composition change and etched phase boundary cause SCC of electropolished surface. Machining produces a nanocrystalline layer and an underlying deformed layer. Elongated ferrite phases in nanocrystalline layer increase SCC of machined surface. Abstract: Effect of surface treatments on microstructure and stress corrosion cracking (SCC) of 308L weld metal in primary pressurized water reactor environment was evaluated by microstructure characterization and bent beam tests. The results showed that no SCC was observed on colloidal silica slurry polished surface while the change in composition and etched phase boundary promote SCC initiation after electropolishing. Further, milling and grinding produce a nanocrystalline layer and an underlying deformed layer on the surface. The nano-sized δ ferrite phase has a detrimental effect on SCC due to the synergistic effect of high concentration of dislocations and its nano size.